Adsorption of Copper and Zinc from Aqueous Solutions by Bentonite - TOMUL*, FATMA; TURGUT BASOGLU†, FUNDA (Asian Journal of Chemistry, 2009)
Bentonite has been used as an adsorbent for the removal of Cu2+and Zn2+ ions from aqueous solutions via adsorption. The effect of theadsorbent amount, pH of suspension, solution concentration and temperatureand the contact time on adsorption was investigated. The amountof Cu2+ and Zn2+ ions adsorbed increased with increasing adsorbentamount, pH and temperature and with decreasing concentration. Theadsorption parameters were obtained using Reciprocal Langmuir,Langmuir, Linear Freundlich, Freundlich and Langmuir-Freundlichisotherm models by use of non linear regression analysis. The adsorptionisotherm studies indicated that adsorption was consistent with the ReciprocalLangmuir isotherm model. Results of the thermodynamic studiesindicated that the adsorption of both ions on bentonite was spontaneousand favourable and an endothermic nature of adsorption. A pseudosecondorder equation described the adsorption process for either Cu2+or Zn2+. The results of this study demonstrated that the bentonite is apotential adsorbent for the removal of Cu2+ and Zn2+ ions from aqueoussolutions.